Starting a Glaucoma Fellowship in Pakistan: A Critical Step toward Enhancing Eye Care: Doi: 10.36351/pjo.v40i4.1942 - Malik, Tayyaba Gul; Zia, Rashid (Pakistan Journal of Ophthalmology, 2024)
The prevalence of glaucoma in Pakistan, as in many developing countries, poses a significant challenge to the healthcare system. Globally, glaucoma is the second leading cause of blindness, affecting millions, often progressing